Addition and Subtraction of Integers with a Realistic Mathematics Education Approach - Mara Samin Lubis (IAI Ma'arif NUMetro Lampung, 2023)
The aim of this research is to analyze the existing mathematics curriculum at the MIN Medan school and to identify how whole numbers are currently taught at the school. In addition to exploring and developing teaching strategies that incorporate real-world contexts for teaching integer addition and subtraction, to determine the effectiveness of the Realistic Mathematics Education approach in teaching integer addition and subtraction. The  Realistic  Mathematics Education  (RME)  Approach  is  one possible method. Through circumstances they can really experience, the RME technique offers pupils a learning opportunity to comprehend mathematical  ideas. The  learning  process  for  adding  and  subtracting integers  using  the  RME  approach  is  described  in  this  study using  a qualitative descriptive  methodology. Up to 30  pupils  from  class  IIA served as research subjects for the study, which  was carried out at MIN Medan. Data were gathered using observation notes and pictures. Data were gathered using observation notes and pictures. Data were  reduced,   displayed,   and   concluded, after   which   they   were descriptively narrated. The results showed an effective learning process when the  RME  Approach  was  applied to  the  topic  of  addition  and subtracting integers over the course of five meetings Keywords: Addition Subtraction Mathematic, Realistic Mathematics Education